2021
DOI: 10.1101/2021.12.13.21267748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A meta-analysis of Early Results to predict Vaccine efficacy against Omicron

Abstract: In the studies to date, the estimated fold-drop in neutralisation titre against Omicron ranges from 2- to over 20-fold depending on the study and serum tested. Collating data from the se results in a combined estimate of the fold drop in neutralisation titre against Omicron of 9.7 (95%CI 5.5-17.1). We use our previously established model to predict that six months after primary immunisation with an mRNA vaccine, efficacy for Omicron is estimated to have waned to around 40% against symptomatic and 80% against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 7 publications
2
65
0
Order By: Relevance
“…For these vaccine regimens, we estimate that the boosting with PF (used in both regimens) increases NATs by 1.5-fold (95% credible interval, CrI 1.4–1.8) compared to NATs following dose 2 of PF and 3.0-fold (95% CrI 2.5– 3.9) compared to NATs following dose 2 of AZ, resulting in similar NATs following the boost regardless of the primary course. We estimate a 3.9-fold (95% CrI 2.9–5.5) reduction in NATs against the Omicron variant compared to the Delta variant (20) which translates to approximately a 10–23-fold drop in NAT compared to WT, consistent with a meta-analysis of NAT studies 26 . This drop in NATs matches the observed drop in vaccine efficacy against mild disease.…”
Section: Resultssupporting
confidence: 80%
“…For these vaccine regimens, we estimate that the boosting with PF (used in both regimens) increases NATs by 1.5-fold (95% credible interval, CrI 1.4–1.8) compared to NATs following dose 2 of PF and 3.0-fold (95% CrI 2.5– 3.9) compared to NATs following dose 2 of AZ, resulting in similar NATs following the boost regardless of the primary course. We estimate a 3.9-fold (95% CrI 2.9–5.5) reduction in NATs against the Omicron variant compared to the Delta variant (20) which translates to approximately a 10–23-fold drop in NAT compared to WT, consistent with a meta-analysis of NAT studies 26 . This drop in NATs matches the observed drop in vaccine efficacy against mild disease.…”
Section: Resultssupporting
confidence: 80%
“…Previous in vitro studies already showed the association of some of these mutations with increased infectivity, ACE2 interaction (N501Y, P681H) (Gong et al, 2021;Saito et al, 2021), or immune evasion (K417N, N440K, G446S, S477N, E484A/K, Q493R) (Baum et al, 2020;Clark et al, 2021;Greaney et al, 2021aGreaney et al, , 2021bGreaney et al, , 2021cLiu et al, 2020;Rappazzo et al, 2021;Starr et al, 2021;Weisblum et al, 2020). This unprecedented accumulation of Spike mutations raised concern about a major antigenic drift that could significantly decrease the efficacy of current vaccines (Andrews et al, 2021;Khoury et al, 2021;Schmidt et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Using an analysis that synthesizes recent neutralization results with prior experiments to correlate vaccine efficacy against infection (35,36), we can infer the relative reduction in protection due to BA.1 versus Delta, which we presume is the primary circulating variant in the background transmission.…”
Section: Estimating the Plausible Range For Immune Escapementioning
confidence: 99%